Counts of diatom valves for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010 - Plikk, Anna; Engels, Stefan; Fernández-Fernández, Maria; Katrantsiotis, Christos; Kylander, Malin E; Löwemark, Ludvig; Salonen, Sakari; Väliranta, Minna; Helmens, Karin (PANGAEA, 2025)
This dataset provides counts of diatom valves for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010. Counts per taxon are presented against both depth (m) and age (ka BP); total sums for classes of diatoms (e.g. total benthic diatoms) and overall counts are presented as well. The diatom dataset provides information on Eemian lake ecosystem dynamics. A total of 104 samples were selected for diatom analysis. Diatoms were extracted from the sediment following the protocol presented by Battarbee et al. (2003). First, organic matter was oxidized in H2O2 in a water bath (at c. 100 °C). Subsequently, carbonates were removed by 10% HCl treatment (no visible reaction). Clay particles were decanted from 100 ml beakers after sedimentation overnight. Sand grains were removed after five seconds of sedimentation. The residue was mounted in Naphrax® and analysed under a light microscope with X1000 magnification using immersion oil. Flora used for species identification and information on ecological preferences are presented in Plikk et al. (2016; 2021). A minimum of 400 diatoms were identified from each sample with the exception of the bottommost samples where diatom abundance was very low. All analyses were performed in the laboratories Stockholm University, Sweden.
Keywords: Chironomids; C/N; Diatom; Eemian; Finland; Itrax; loss on ignition; macrobotanical remains; MIS 5e; n-alkanes; non-pollen palynomorphs; Pollen; Sokli; stabe isotopes